2022
DOI: 10.3389/fsufs.2022.977121
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of humic-based products on the microbial community structure and functions toward sustainable agriculture

Abstract: Humic-based products (HPs) are carbon-rich organic amendments in the forms of extracted humic substances from manure, compost, and raw and extracted forms of lignites, coals and peats. HPs are widely used in agriculture and have beneficial effects on plants. While the agronomic benefits of HPs have been widely reported, information on their impact on the soil microbial community composition and functions is lacking, despite claims made by companies of humic substances as biostimulants. In this review, we explo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 115 publications
1
7
0
Order By: Relevance
“…Consequently, it is possible to conclude that wheat cultivation favors DHA maintenance. This is in agreement with previous findings [43], that wheat cultivation has a more favorable effect on the maintenance of biological properties than oat cultivation, as confirmed by the higher indices of dehydrogenase and respiration activities, microbial biomass and DNA content recorded on sites where wheat was grown [43].…”
Section: Soil Enzymatic Activitysupporting
confidence: 93%
See 1 more Smart Citation
“…Consequently, it is possible to conclude that wheat cultivation favors DHA maintenance. This is in agreement with previous findings [43], that wheat cultivation has a more favorable effect on the maintenance of biological properties than oat cultivation, as confirmed by the higher indices of dehydrogenase and respiration activities, microbial biomass and DNA content recorded on sites where wheat was grown [43].…”
Section: Soil Enzymatic Activitysupporting
confidence: 93%
“…Intriguingly, despite the high activity of oxyreducing enzymes, the value of the E4/E6 ratio in soils after wheat cultivation was significantly lower compared to soils after rapeseed harvest; nevertheless, it is concluded that the presence of humic substances has a significant effect on the enzymatic activity of dehydrogenases and other soil enzymes. The different fractions that make up the humic layer can have an inactivating effect on their action-the enzymes are incorporated into the structure of the humic substance molecule [43].…”
Section: E4/e6 Ratiomentioning
confidence: 99%
“…These bioactive compounds activate the signal transduction pathways, reprogramming the expression of a large subset of genes involved in plant growth and development processes such as nutrient uptake and assimilation, photosynthesis, respiration, and primary and secondary metabolism (Canellas & Olivares, 2014; Jannin et al., 2012; Nardi et al., 2017, 2018; Rathor et al., 2023; Zanin et al., 2018). Indirect effects involve the soil environment where HPs improve soil physiochemical and biological properties such as soil structure, texture, water retention capacity, soil pH, enhanced nutrient availability due to the ability of HPs to form complexes with ions that prevent leaching losses, and alterations in microbial abundance and biodiversity (Dawood et al., 2019; García, de Souza, et al., 2016a; García‐Mina et al., 2004; Gerke, 2021; Lumactud et al., 2022). These improvements in soil physicochemical and biological properties contribute to a healthy soil environment leading to improved plant performance and increased yield, as observed in HP‐supplied plants.…”
Section: Introductionmentioning
confidence: 99%
“…These compounds are the pool of organic carbon produced through extensive biological and chemical transformation of dead biota ( Canellas et al , 2015 ). Among different fractions of HSs, HA is the main component with a more complex structure that makes it a high molecular weight compound, which is recalcitrant to microbial degradation in soil ( Ahmad et al , 2018 ; Lumactud et al , 2022 ). Several studies have reported the bio-stimulatory effects of humic acid in improving plant growth and development ( Canellas et al , 2002 ; Muscolo et al , 2007 ; Schmidt et al , 2007 ; Zandonadi et al , 2007 ; Mora et al , 2010 , 2014 ; Trevisan et al , 2010 ; Olaetxea et al , 2019 ; Zanin et al , 2019 ; Souza et al , 2022 ).…”
Section: Introductionmentioning
confidence: 99%